Compressive Strength of Concrete Containing Recycled Glass Powder - Nugraha, Bimantara Putra; Sudjatmiko, Eddy Triyanto; Bali, Ika (President University, 2023)
Glass bottle waste takes a million years to decompose. Recycling is the best option to solve this problem. Onealternative is to use recycled glass in the form of powder as a material for making concrete. This study proposes theuse of recycled glass powder as a concrete material to partially substitute fine aggregate. This study aims todetermine the effect of glass powder as a partial substitute for fine aggregate on the compressive strength of concrete.Partial substitution of fine aggregate was selected with a percentage of 5%, 10%, and 15%. Standard cylindricalspecimens aged 28 days used in compressive strength testing in this study. Then, the test results of concretecontaining recycled glass powder compared to ordinary concrete. The test results show that the compressive strengthof concrete containing 15% recycled glass powder gives an average compressive strength of 35.57 MPa which isslightly higher than the compressive strength of normal concrete of 35.10 MPa. This study found that the use of glasspowder as a substitute for fine aggregate can be used as a substitute for normal concrete in terms of compressivestrength and reduce glass waste.